Chordoma: study of five cases - B Sigdel; R Baidya (Association of Clinical Pathologists of Nepal, 2012)
Background: Chordoma is a rare slow growing but malignant midline bone tumor arising from the notochordal remnant and recapitulates the notochord at various stages of differentiation. They involve the axial skeleton. The aim of this study was to find the frequency of this tumor and to analyze the clinical, radiological and pathological findings. Materials and Methods: Cases of chordoma diagnosed at B & B Hospital from January 1999 to November 2011 were studied for clinicopathologic features and immunohistochemical profile. Results: There were 5 cases of chordoma during the study period. Females were affected more with male to female ratio of 1:1.5. Sixty percent of the tumors involved the sacrum, while 40% were intracranial and located at the base of the skull. Median age of diagnosis was 44.8 years. Four cases (80%) were conventional chordoma and 1 case (20%) was a chondroid variant. Two cases evaluated were immunoreactive for S-100 protein, pan-cytokeratin and EMA. Conclusion: Though a low grade tumor with prolonged clinical course, chordomas can cause extensive local destruction with significant morbidity and mortality. Hence a prompt diagnosis with adequate excision is important to save the patient's life. Journal of Pathology of Nepal (2012) Vol. 2, 260-264 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6874